2001
DOI: 10.1093/ndt/16.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of anti‐neutrophil cytoplasmic antibodies (ANCA): frequency and specificity in a sample of 191 homozygous (PiZZ) alpha1‐antitrypsin‐deficient subjects

Abstract: ANCA not directed against classical antigens (MPO and PR3) may be found in PiZZ patients. However, these patients do not develop systemic vasculitis features. Therefore, alpha1-antitrypsin deficiency is not sufficient to induce ANCA positive vasculitides, and may only act as a second hit amplifying factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 35 publications
1
22
0
1
Order By: Relevance
“…The possibility of false positive results because of nonspecific binding or rheumatoid factor binding to the monoclonal captured antibody could be easily excluded by using a control plate coated with an unrelated monoclonal antibody of the same isotype as the captured one. Using PR3 capture ELISA, the correlation between ELISA antibody titres and either the IIF results or the disease activity is better than with direct ELISA [30]. The PR3 capture ELISA showed a significantly higher sensitivity in patients with WG with renal involvement compared to cANCA IIF (85% versus 58%) [59].…”
Section: Elisamentioning
confidence: 94%
See 2 more Smart Citations
“…The possibility of false positive results because of nonspecific binding or rheumatoid factor binding to the monoclonal captured antibody could be easily excluded by using a control plate coated with an unrelated monoclonal antibody of the same isotype as the captured one. Using PR3 capture ELISA, the correlation between ELISA antibody titres and either the IIF results or the disease activity is better than with direct ELISA [30]. The PR3 capture ELISA showed a significantly higher sensitivity in patients with WG with renal involvement compared to cANCA IIF (85% versus 58%) [59].…”
Section: Elisamentioning
confidence: 94%
“…ANCA that are not directed against classical antigens, such as PR3 and MPO, may be found in PiZZ patients, usually free from systemic vasculitis features. It seems that A1T deficiency is not sufficient to induce ANCA vasculitis, being merely a hit-amplifying factor [30].…”
Section: Laboratory Considerations For Setting Clinically Meaningful mentioning
confidence: 99%
See 1 more Smart Citation
“…Actually a subpopulation of al-AT deficiency PiZZ patients associated with ANCA-positivesystemic vasculitis has been reported, but it was demonstrated there is no evidence that a PiZZ patient carrying ANCAagainst PR3 or MPOhas a greater risk of developing systemic vasculitis than a PiMM patient carrying ANCA (38). Although the vasculitis associated with al-AT deficiency showed a more widespread and worse prognosis than vasculitis, in PiMMpatients, there was no difference in age at onset or relapse tendency (39).…”
Section: Case Reportmentioning
confidence: 97%
“…Rarok et al [20] have recently become the first investigators to claim a larger mPR3+ subset as a risk factor for relapse in patients with Wegener's granulomatosis. Previously, the PiZ allele, conferring lower · 1 -antitrypsin (A1AT) activity (the major in vivo PR3 inhibitor), has been associated with poorer outcome in patients with ASV although not with the development of ASV per se [22,23]. Rooney et al [24] more recently reported that in vitro neutrophil activation by PR3-ANCA was attenuated in the presence of exogenous A1AT.…”
mentioning
confidence: 99%